Analysis of Indonesia's Protectionism Policy Challenges Amidst the Rise of Imported Products from China - Setyowati, Nugraheni; Riani, Lilia Pasca (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This paper aims to determine empirically the challenges of protectionist policies set by the Indonesian government to protect the interests of local producers and consumer needs due to the rampant products imported from China. Design/Methode/Approach : This research uses a literature study method (library research) with an approach using secondary data from various credible written sources and relevant to Economics and Free Trade, especially Imports from China. The data analysis technique uses content analysis techniques and qualitative descriptive analysis. Research Finding : Based on the results of the data analysis, this study found that various complex challenges faced in line with the context of globalization and free trade agreements that limit Indonesia's space to implement protectionist policies. Theoretical contribution/Originality : This research deepens the knowledge of free trade policy literature by highlighting the complexity of protectionism implementation challenges in developing countries, namely Indonesia. Practitionel/Policy implication : This research underlines the need for a strategy to strengthen domestic industries before implementing protectionism in order to be more competitive in the global market, one of which is to avoid the negative impact of trade retaliation. Research limitation : As this research only focuses on analyzing protectionism policies between Indonesia and imported products from China.